TOURISM POLICY IN LATVIA - FROM A TOP-DOWN TO A COLLABORATIVE APPROACH - Rozite, Maija; van der Steina, Aija; Kalniņa, Ilona (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
In 2019, Latvia drafted a National Development Plan [NDP 2027] for the next period, which also comprises actions for the development of the tourism sector. Unlike previous practices, approaches to drafting a common plan and developing and implementing tourism policy have changed significantly.The aim of the research is to describe the process of developing a tourism development plan, analyse the use of the latest planning and policy implementation approaches and evaluate the framework of the plan.A qualitative research strategy - a case study was used. The main research methods are document analysis, in-depth interviews and participatory observations.The process of drafting a new tourism policy and action plan, its main stages, tasks, methods, key stakeholders and discussions and the various documents elaborated has been summarized as a result of the research. The main problems related to the implementation of a bottom-up collaborative approach - lack of competencies of individual stakeholders, dominance of municipal interests, conviction that problems can only be solved from above, centrally, using state budget resources - have been identified.The document analysis shows that the tourism policy document drafted differs significantly from previous documents. It incorporates the need for collaboration between tourism destinations, local municipal organizations and defines productivity as a transversal criterion for action.